2016
DOI: 10.1371/journal.pone.0150635
|View full text |Cite
|
Sign up to set email alerts
|

Foxn1 Transcription Factor Regulates Wound Healing of Skin through Promoting Epithelial-Mesenchymal Transition

Abstract: Transcription factors are key molecules that finely tune gene expression in response to injury. We focused on the role of a transcription factor, Foxn1, whose expression is limited to the skin and thymus epithelium. Our previous studies showed that Foxn1 inactivity in nude mice creates a pro-regenerative environment during skin wound healing. To explore the mechanistic role of Foxn1 in the skin wound healing process, we analyzed post-injured skin tissues from Foxn1::Egfp transgenic and C57BL/6 mice with Wester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
112
0
13

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(133 citation statements)
references
References 48 publications
(91 reference statements)
8
112
0
13
Order By: Relevance
“…In the last, remodeling phase, all the signals that were rapidly evoked are ceased, and disorganized collagen fibers form scar tissue (6). FOXN1 was reported by our team as a damage response signal during the first two phases of wound healing, and we consider FOXN1 responsible for scar formation (40). In our studies, the levels of FOXN1 expression have clearly been raised in all keratinocytes except basal ones at the wound margin and the postinjury epithelium.…”
Section: Role Of Foxn1 In the Skinsupporting
confidence: 55%
See 2 more Smart Citations
“…In the last, remodeling phase, all the signals that were rapidly evoked are ceased, and disorganized collagen fibers form scar tissue (6). FOXN1 was reported by our team as a damage response signal during the first two phases of wound healing, and we consider FOXN1 responsible for scar formation (40). In our studies, the levels of FOXN1 expression have clearly been raised in all keratinocytes except basal ones at the wound margin and the postinjury epithelium.…”
Section: Role Of Foxn1 In the Skinsupporting
confidence: 55%
“…Similarly to FOXN1, Notch is a prodifferentiation factor (48), and recently it has been reported to act as an injury response signal in the inflammatory and proliferation phases of wound healing in suprabasal keratinocytes (49). This process mirrors the postwounding expression of Foxn1 (40). This observation supports their common function in the BMP/Notch signaling pathway suggested in HFs (45).…”
Section: Foxn1 Involvement In Signaling Pathwaysmentioning
confidence: 56%
See 1 more Smart Citation
“…Foxn1, a potent mammalian wound healing factor, also appears to be involved in EMT-driven re-epithelialization during repair, as evidenced by studies in Foxn1 transgenic mice. In these mice, the induction of EMT post-wounding was demonstrated though the upregulation of EMT transcriptional regulator Snail1, increased MMP9 expression, presence of vimentin+/E-cadherin+ cells, and migratory keratinocytes at the wound edge expressed Foxn1 which co-localized with Snail (Gawronska-Kozak, et al, 2016). Finally, zebrafish keratocytes in explant culture, which serve as a well-studied model of epithelial wound healing, display evidence of EMT (McDonald, et al, 2013).…”
Section: Emt In Physiologic Tissue Repairmentioning
confidence: 99%
“…Moreover, our recent data revealed that Foxn1 can act as a regulator of the skin wound healing process. The experiments performed on Foxn1::Egfp transgenic mice showed that Foxn1-bearing cells participate in the wound healing process through engagement in re-epithelialization and possible involvement in scar formation due to Foxn1 activity during the epithelial-to-mesenchymal transition (EMT) [12]. In the present study using next-generation high-throughput DNA sequencing techniques, we aimed to test the hypothesis that Foxn1 expression in the skin is an essential condition for establishing the adult skin phenotype and that a lack of Foxn1 maintains skin in a neoteny stage (immature stage of development).…”
Section: Introductionmentioning
confidence: 99%